1999
DOI: 10.1038/sj.bjc.6690196
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of c-erbB2 is an independent marker of resistance to endocrine therapy in advanced breast cancer

Abstract: The present study investigated the interaction between c-erbB2 overexpression and the response to first-line endocrine therapy in patients with advanced breast cancer. The primary tumours of 241 patients who were treated at first relapse with endocrine therapy were assessed for overexpression of c-erbB2 by immunohistochemistry. c-erbB2 was overexpressed in 76 (32%) of primary breast cancers and did not correlate with any other prognostic factor. The overall response to treatment and time to progression were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
87
0
8

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(100 citation statements)
references
References 44 publications
5
87
0
8
Order By: Relevance
“…In the whole group of patients, including 247 OR-positive, 139 ORnegative and eight OR-unknown cases, overexpression of cyclin A and of Neu were indicative of worse outcome, with P values of 0.0195 and 0.0151 respectively (Table 3). Neu overexpression already has previously been reported to be associated with a worse prognosis (Slamon et al, 1987) and more recently was found to be indicative of tamoxifen resistance (Houston et al, 1999;Stal et al, 2000). The prognostic value of cyclin A overexpression may well be contributed to its interaction with large sized, undifferentiated, OR-negative breast tumours with an increased proliferative capacity (Table 4).…”
Section: Discussionmentioning
confidence: 86%
“…In the whole group of patients, including 247 OR-positive, 139 ORnegative and eight OR-unknown cases, overexpression of cyclin A and of Neu were indicative of worse outcome, with P values of 0.0195 and 0.0151 respectively (Table 3). Neu overexpression already has previously been reported to be associated with a worse prognosis (Slamon et al, 1987) and more recently was found to be indicative of tamoxifen resistance (Houston et al, 1999;Stal et al, 2000). The prognostic value of cyclin A overexpression may well be contributed to its interaction with large sized, undifferentiated, OR-negative breast tumours with an increased proliferative capacity (Table 4).…”
Section: Discussionmentioning
confidence: 86%
“…However, no synergistic or additive activity has been reported with gefitinib and a cytotoxic agent in phase III clinical trials Johnson et al, 2002). Furthermore, it has been suggested that high expression of EGFR or HER2 causes the development of acquired endocrine resistance in endocrine-responsive breast cancer (Benz et al, 1993;Houston et al, 1999). Therefore, it might be possible that gefitinib will enhance the antitumour effect of endocrine agents.…”
Section: Discussionmentioning
confidence: 99%
“…Rationales of this hypothesis are follows: (1) clinical studies have suggested that ER-positive breast cancers with a high expression level of EGFR or HER2 are frequently resistant to endocrine therapy and have a shorter survival time (Sainsbury et al, 1987;Nicholson et al, 1989;van Agthoven et al, 1992;Newby et al, 1995;Dowsett et al, 2001), (2) artificially increasing expression of EGFR or HER2 to high levels in ER-positive breast cancer cells leads to an antioestrogen-resistant phenotype (Benz et al, 1993;Houston et al, 1999), (3) a prolonged exposure of an antioestrogen to ERpositive breast cancer cells sometimes results in upregulation of EGFR or HER2 expression and an antioestrogen-resistant phenotype (Long et al, 1992;McClelland et al, 2001;Nicholson et al, 2002), (4) we and others have suggested that an anti-HER2 monoclonal antibody or inhibitor of HER2 signalling pathway enhances an antitumour effect of antioestrogens in ER-positive breast cancer cells with a moderate or high level of HER2 expression (Witters et al, 1997;Kunisue et al, 2000;Kurokawa et al, 2000). Actually, combination therapy with trastuzumab and an endocrine agent, the aromatase inhibitor anastrozole, has been tested in a clinical trial (Winer and Burstein, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all patients with positive ER, however, benefit from endocrine therapy. 2 It is being recognized increasingly that a variety of other growth factors, their receptors and their signaling pathways interact with ER signaling to suppress or stimulate the growth of ER-positive breast cancers. Clinical studies have shown that the response rate to TAM is reduced from 50% in ER-positive breast cancers with normal Her2/neu expression to 17% in ER-positive breast cancers with Her2/neu overexpression.…”
mentioning
confidence: 99%